Tuturan Direktif Naskah Sandiwara Radio serta Penerapannya dalam Pembelajaran Bahasa Jawa SMP (Piwulang : Jurnal Pendidikan Bahasa Jawa, 2023)
Radio play scripts can be used in Javanese language learning in junior high schools as a language teaching medium for students considering that play scripts are built by physical structures, namely language and inner structure which means semantics, thus causing the possibility of polysemy in speech making language learning for junior high school students considered sufficient. it is important to enlarge, especially research studies in Javanese directive utterances. This research is expected to contribute to increasing the study of the Javanese language and students can understand the implied meaning of utterances that are usually expressed by older people. The purpose of this study is to describe the form of directive utterances in radio play scripts in order to add to the study of the Javanese language. This research is a qualitative descriptive study using content analysis methods through a pragmatic approach to data sources for Mapan and Munthu Wijaya radio plays. The result of this research is an analysis of the forms of directive speech acts including Requestives, Questions, Requirements, Prohibitives, Permissives, Advisories of Mapan and Munthu Wijaya radio plays. Based on the research results of Mapan and Munthu Wijaya's radio plays, there are 43 data of directive speech acts that are relevant to the Javanese language learning materials, particularly for KD 4.3, Writing and Presenting Drama Text, which is present in Javanese language subject syllabus for 9th-grade students in Merdeka Curriculum It is hoped that teachers can be more varied in choosing teaching materials and this research can be developed by other researchers with broader studies.